Dark excitons and hot electrons modulate exciton-photon strong coupling in metal-organic optical microcavities - Kolesnichenko, Pavel V.; Hertzog, Manuel; Hainer, Felix; Kefer, Oskar; Zaumseil, Jana; Buckup, Tiago (ACS photonics, 2025)
Polaritons, formed as a result of strong hybridization of matter with light, are promising for important applications, including organic solar cells, optical logic gates, and qubits. Owing to the large binding energies of Frenkel excitons (matter), strong matter-light coupling phenomena are possible at room temperature, high exciton densities, and even with low-quality factor microcavities. In such cases, because of the high degree of delocalization of polaritons, simultaneous effects from dark excitons and hot electrons may affect the performance of potential devices. Their understanding, therefore, is of high importance, but their disentanglement in optical spectroscopy has thus far remained unattainable. Here, we overcome this challenge by careful and systematic analysis of transient polaritonic spectra, supported by analytical models. In doing so, we conclude that dark excitons affect the strength of exciton-photon coupling and manifest themselves as Fano-like polaritonic gain-loss spectra. Free electrons add an additional loss component and imprint two-temperature dynamics on the polaritonic response. The general methodology developed can be applied to a variety of other microcavity structures. Our findings are significant for distinguishing polaritons and other excitations in studies of polariton-electron and plasmon-electron coupling phenomena, as well as photonic control over photophysical and photochemical processes.
Online veröffentlicht: 11. Juni 2025
Gesehen am 15.10.2025